PERBEDAAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR DAN MEDIA ALAT PERAGA PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI IPA SMA PRAYATNA MEDAN - Nur Ainun; M. Yususf Nasution; Risna Wati (Jurnal Pelita Pendidikan, 2017)
Research to know what available distinctive result studies by use of image media and displaytool medias. Observational type that is utilized is experiment by give conduct to on the twoobservational sample group. Population in observational it is exhaustive student braze XI IPA SMAPrayatna Field which is as much 4 classes by totals students 146 person. Observational sample to betaken two prescribed class arbitrarily, which is. Experiment class (XI IA2) and Experiment class (XIIA3) each as much 38 students. Instrument that is utilized in this research is essay deep shapedobjektifitas which is for postest's problem as much 20 problems that their was declared for valid andreliabel. Before beforehand hypthosts testing to be tested normality and homogeneity esays.Normality is tested by use of tech Liliefors and homogeneity by use of quiz F. Of examination thatdoes to be gotten that sample second gets normal distribution and homogeneous. Acquiredobservational result that yielding average studies that chastened utilizes media image and displaytool media usufructs acquired hypthosts testing t computing >t table which is 7.98 > 0.78 on level =0.05. Students learned result braze . Experiment to be gotten postest's average as big as 82.76.Meanwhile beajar's result student brazes Experiment II. postest's average as big as 76 . 44.Key word: Students Learned result Media Draw and display Tool Media